The influence of Genetic Factors on Development of Malocclusions - Çağlar Sakin; Gökmen Kurt (Galenos Yayinevi, 2009)
The relative influence of genes and environmental factors in the aetiology of malocclusion has been a matter for discussion throughout many years in the orthodontic literature. The aetiology of malocclusion is mostly multifactoriel and heredity is being stressed as an aetiologic factor in recent years. More precise information will be gained on the aetiology of malocclusion and its treatibility, if we can differentiate the effect of genes and environment on the dentofacial deformity in a particular individual. if the problem is genetic, orthodontists will be restricted about what they can do or what they can change. The purpose of this review is to explain to what degree and how the den-tofacial structures will be influenced by genetic and environmental factors.